LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING UNTUK MENINGKATKAN KETERAMPILAN PENGAMBILAN KEPUTUSAN KARIR KELAS XII DI SMK CENDEKIA - Rizqi Hervian Santoso; Fatimah, Siti; Alawiyah, Tuti` (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
Career decision making is a selection process from a variety of existing career options, whichcan be taken based on self-understanding, one's personality, and self-motivation. It can includeeducation as well as entering a training program, applying for a job, upgrading a job, changingpositionsorenteringanewjob.ThereasonforthisreviewwastodecidetheviabilityofgatheringdirectionadministrationsutilizingpretendingprocedurestofurtherdeveloptheprofessionthinkingabilitiesofclassXIIatSMKCendekia.Thereweretwogroupsandaquasi-experimentalnon-equivalent control group design in this study. This exploration was directed on 20 class XIIunderstudies who were partitioned into an exploratory gathering and a benchmark group. TheinformationassortmentstrategyutilizedwasaconfidencepollalludingtoKrumboltz'shypothesis. Using SPSS version 25 and a gain score, quantitative data analysis methods wereapplied to the data. This study's n-gain test results show that the experimental group's averagevalueis58.6%,whichisconsideredmoderatelyeffective.Meanwhile,therunofthemillworthofthebenchmarkbunchinthen-gaintestwas35.9%,whichwasintheineffectiveclass.Soitmightbe assumed that pack course organizations using imagining techniques are truly feasible inadditional creatingoccupation decisiveabilitiestoreasonfor classXII atSMKCendekia.